Eksplorasi Ragam Jenis Penelitian Dalam Kajian Pendidikan Islam Kontemporer - Ana Cahayani Fatimah; Muhlar Muhlar; Andi Fitriani Djollong (Institut Agama Islam Hidayatullah Batam, 2025)
This study aims to explore the various types of research used in contemporary Islamic education studies, including qualitative, quantitative, mixed methods, classroom action research, research and development (R&D), systematic reviews, and bibliometrics. This study is structured in an analytical literature review format, reviewing recent articles, proceedings, and research reports. The results indicate that method diversification is increasingly prominent in the digital era, with the increasing use of mixed methods and bibliometrics, while qualitative research remains the most dominant approach in value-based, cultural, and practical studies of Islamic education. This study emphasizes the importance of selecting appropriate methods according to research objectives and the need to strengthen the methodological capacity of Islamic education researchers.